STUDY OF COMPLEMENTARY AND ALTERNATIVE MEDICINE USAGE OF CANCER PATIENTS RECEIVING MEDICAL ONCOLOGY CLINIC MEDICINE AND ITS RELATIONSHIP WITH THEIR LIFE QUALITY. - Temucin, Elif; Ortabag, Tulay (ONCOLOGY NURSING SOC, 2016)
…